A comparative assessment of regional representativeness of EDGAR and ECLIPSE emission inventories for air quality studies in India. (15th February 2020) - Upadhyay, Abhishek; Dey, Sagnik; Goyal, Pramila
Abstract: Ambient PM2.5 (fine particulate matter) exposure is one of the leading health risk factors in India. The role of chemical transport models (CTMs) in air quality management is well recognized today. However, effectiveness of CTM outputs critically depends on accuracy of emission inventory. Here we evaluate anthropogenic PM2.5 simulated by WRF-Chem using two major inventories - EDGAR and ECLIPSE with satellite and MERRA-2 reanalysis data. We found that both inventories show similar accuracy statistically (correlation coefficients, R of 0.87 and 0.9 and RMSEs of 8.4 and 10.2 μg/m³ for EDGAR and ECLIPSE, respectively) at national scale, but with significant regional variation. The simulated anthropogenic populated PM2.5 exposure is high with ECLIPSE emission compare to EDGAR for most of the states. In some populated states Delhi, Uttar Pradesh, Haryana, Bihar, Uttarakhand, Rajasthan, Punjab and few less populated states Sikkim, Tripura exposure is exceeding more than 30% with ECLIPSE emission inventory compare to EDGAR. After the monsoon is withdrawn, pollution builds up in the western Indo-Gangetic Basin (IGB), while it is pushed towards eastern IGB in the winter season. Diurnal amplitude in anthropogenic PM2.5 exceeds 15  μ g / m 3 in large parts of India especially during the post-monsoon to winter season suggesting that exposure modeling needs to be carried out with higher temporal frequency for better health burden assessment. Graphical abstract: Image 1 Highlights: Anthropogenic PM2.5 is simulated over India with EDGAR-HTAP and ECLIPSE emission Inventory. Anthropogenic PM2.5 using ECLISPE is 26% higher than that using EDGAR inventory. BC:OC ratio simulated by both the inventories varies in the range 3–5. Pollution build-up is pushed towards eastern part of Gangetic basin in the winter season. Diurnal amplitude in PM2.5 often exceeds 15  μ g/m 3 .